2008
DOI: 10.1007/s12185-008-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem examination of the kidney in allogeneic hematopoietic stem cell transplantation recipients: possible involvement of graft-versus-host disease

Abstract: To investigate the association between graft-versus-host disease (GVHD) and renal injury after allogeneic stem cell transplantation (allo-SCT), we compared autopsy findings of 26 consecutive allo-SCT recipients with two control groups: patients with hematologic malignancies who received cytotoxic chemotherapy alone (Control 1, n = 21) and those with non-hematologic diseases (Control 2, n = 12). We evaluated the following renal pathology; renal tubulitis, allograft glomerulitis, intimal arteritis, allograft nep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
3
28
2
Order By: Relevance
“…23,38,40 In their study of 26 autopsy cases, El-Seisi et al 38 noted substantial interstitial fibrosis, as we found in our group, but they also found tubulitis of unspecified degree in 67% of autopsied hematopoietic cell transplant patients, although they did not find an association of tubulitis with clinical GVHD. In a study of seven hematopoietic cell transplant patients with thrombotic microangiopathy, Mii et al 23 noted mild or moderate interstitial inflammation in all patients (two biopsy, five autopsy).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…23,38,40 In their study of 26 autopsy cases, El-Seisi et al 38 noted substantial interstitial fibrosis, as we found in our group, but they also found tubulitis of unspecified degree in 67% of autopsied hematopoietic cell transplant patients, although they did not find an association of tubulitis with clinical GVHD. In a study of seven hematopoietic cell transplant patients with thrombotic microangiopathy, Mii et al 23 noted mild or moderate interstitial inflammation in all patients (two biopsy, five autopsy).…”
Section: Discussionsupporting
confidence: 58%
“…8,14,16,19,38,39 A few single-center studies of autopsy kidney specimen in the hematopoietic cell transplant population have been reported, including one large study focused primarily on thrombotic microangiopathy. 20,21,38,40 We retrospectively reviewed our single-center experience with renal pathology in specimens from three groups of hematopoietic cell transplant recipients. These included patients with core kidney biopsies for clinical renal dysfunction, in which we characterized three glomerulonephridities not previously reported in the hematopoietic cell transplant population.…”
mentioning
confidence: 99%
“…First, the absence of GVHD in autologous HCT, which can contribute to renal lesion directly through cytokine-and immune-related injury, including glomerular deposits causing nephrotic syndrome, and tubulitis; or indirectly through nephrotoxicity induced by CYA used in prophylaxis against GVHD. [23][24][25] In addition, severe GVHD with diarrhoea and dehydration, and CMV reactivation because of treatment of GVHD with high-dose prednisolone can also contribute to GVHDassociated nephrotoxicity. 26,27 Second, because there are no foreign cells in myeloablative autologous HCT, more rapid engraftment occurs (resulting in less cytopenia, sepsis and nephrotoxicity induced by antimicrobials).…”
Section: Incidence Of Aki Following Hctmentioning
confidence: 99%
“…[23][24][25] In addition, severe GVHD with diarrhoea and dehydration, and CMV reactivation because of treatment of GVHD with high-dose prednisolone can also contribute to GVHD-associated nephrotoxicity. 26,27 CMV reactivation itself increased the risk for the occurrence of AKI in nonmyeloablative HCT.…”
Section: 41mentioning
confidence: 99%
“…First, the absence of GVHD in autologous HCT, which can contribute to renal lesions directly through cytokine-and immune-related injury, including glomerular deposits causing nephrotic syndrome and tubulitis; or indirectly through nephrotoxicity induced by calcineurin inhibitors used in prophylaxis against GVHD. 23,24 Furthermore, severe GVHD with diarrhea and consequent dehydration, as well as CMV reactivation due to treatment of GVHD with high-dose prednisolone can likewise contribute to GVHD-associated nephrotoxicity. 12,25 Second, since there are no foreign cells in myeloablative autologous HCT, engraftment occurs more rapidly (resulting in less cytopenia, sepsis and antimicrobe-induced nephrotoxicity).…”
Section: Incidencementioning
confidence: 99%